Analysis of Water Pollution Levels in Batang Masumai River, Merangin Regency, Jambi Province - Astuti, Syurmi; Saleh, Muhammad Irsan; Arita, Susila; Legiran (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Water pollution is a pressing environmental issue that adversely affects aquatic ecosystems and the usability of water resources. The Batang Masumai River, located in Merangin Regency, Jambi Province, is an essential water source for local communities but faces escalating pollution challenges due to industrial, agricultural, and residential activities. This study analyzes the pollution levels of the Batang Masumai River by assessing seven key parameters: temperature, pH, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). A quantitative observational approach was employed, utilizing secondary data collected from 2021 to 2024. The results were evaluated against Class II water quality standards as stipulated in Government Regulation Number 22 of 2021. The findings indicate that while parameters such as temperature and pH generally adhered to acceptable standards, others, notably TSS, BOD, and COD, frequently exceeded the regulatory limits, particularly in 2021. This suggests substantial pollution stemming from untreated wastewater and soil erosion. Although improvements were observed in subsequent years, several parameters remained problematic, posing ongoing risks to aquatic ecosystems and water resource sustainability. These findings underscore the urgent need for enhanced wastewater treatment systems, stricter enforcement of environmental regulations, and the adoption of sustainable watershed management practices to restore and safeguard the ecological health of the river.